Usulan Manajemen Pengunjung Situs Makam Sunan Kalijaga, Kelurahan Kadilangu, Kabupaten Demak - Musadad Musadad (Faculty of Cultural Sciences, 2018)
Te Sunan Kalijaga tomb complex located in Kadilangu, Demak, Central Java is an archaeologicalsite that have very high signifcance values in terms of history, culture, and economy. Tis tomb complexis always fully-visited by pilgrims from various regions. Te peak season of the tomb visiting periodis in the month of Syafar, one month before Ramadan. At the time, the visitors must be trapped in along queue in the corridor that was prepared by Yayasan Sunan Kalijaga to enter the tomb complex.Tis condition certainly leads inconveniences for pilgrims and it may decrease the site's signifcancevalues. For this reason, eﬀorts are needed to reduce pilgrimage density in the corridors of pilgrimsfrom the entrance gate to the site complex. Alternative proposals to reduce pilgrim density are proposedin two alternatives. Te frst, after the pilgrimage procession reaches and fnishes their pilgrimage,the visitors should go out through another door and pass the south corridor of the mosque to theroad on the east side of the mosque heading south to the ancient lake and heading to the road to theparking lot. Te second proposal is that pilgrims passes through the existing corridor to enter andto exit, but the corridor is divided into two lanes in frm and very strict arrangements. Tis meansthat pilgrims should not enter the wrong lane and there are restrictions on the amount of entry ata time of high density.